Homology modeling of the human 5-HT(1A), 5-HT (2A), D1, and D2 receptors: model refinement with molecular dynamics simulations and docking evaluation - Yap, B.K.; Buckle, M.J.; Doughty, S.W. (2012)
5-HT(1A) serotonin and D1 dopamine receptor agonists have been postulated to be able to improve negative and cognitive impairment symptoms of schizophrenia, while partial agonists and antagonists of the D2 and 5-HT(2A) receptors have been reported to be effective in reducing positive symptoms. There is therefore a need for well-defined homology models for the design of more selective antipsychotic agents, since no three-dimensional (3D) crystal structures of these receptors are currently available. In this study, homology models were built based on the high-resolution crystal structure of the β(2)-adrenergic receptor (2RH1) and further refined via molecular dynamics simulations in a 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) lipid bilayer system with the GROMOS96 53A6 united atom force field. Docking evaluations with representative agonists and antagonists using AutoDock 4.2 revealed binding modes in agreement with experimentally determined site-directed mutagenesis data and significant correlations between the computed and experimental pK (i) values. The models are also able to distinguish between antipsychotic agents with different selectivities and binding affinities for the four receptors, as well as to differentiate active compounds from decoys. Hence, these human 5-HT(1A), 5-HT(2A), D1 and D2 receptor homology models are capable of predicting the activities of novel ligands, and can be used as 3D templates for antipsychotic drug design and discovery.